A comparative study on the position of transgender under civil law and Islamic law / Haffiza Jemali, Idamasliza Maarof and Nor Shazana Sedek Shah - Jemali, Haffiza; Maarof, Idamasliza; Sedek Shah, Nor Shazana (2006)
This research was conducted to determine the position of transgenders under civil and Islamic law as well as their rights and obligations. This topic was chosen because it had never been brought up for discussion despite the fact that transgenders in the society has grown in numbers. Therefore, this issue needs more discussion and explanation for future benefits.